2016
DOI: 10.1016/j.jare.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured lipid carriers for oral bioavailability enhancement of raloxifene: Design and in vivo study

Abstract: The objective of present work was to utilize potential of nanostructured lipid carriers (NLCs) for improvement in oral bioavailability of raloxifene hydrochloride (RLX). RLX loaded NLCs were prepared by solvent diffusion method using glyceryl monostearate and Capmul MCM C8 as solid lipid and liquid lipid, respectively. A full 3(2) factorial design was utilized to study the effect of two independent parameters namely solid lipid to liquid lipid ratio and concentration of stabilizer on the entrapment efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(83 citation statements)
references
References 37 publications
5
72
0
1
Order By: Relevance
“…Figure shows a complete solubilization of leflunomide in lipid matrix or transformation of leflunomide crystal to amorphous form that has been dispersed in the lipid matrix. 20 …”
Section: Resultsmentioning
confidence: 99%
“…Figure shows a complete solubilization of leflunomide in lipid matrix or transformation of leflunomide crystal to amorphous form that has been dispersed in the lipid matrix. 20 …”
Section: Resultsmentioning
confidence: 99%
“…33 Drug (1 g of DOX-GEM and 0.5 g of VCR), Precirol ATO 5 (5 g), and injectable soya lecithin (10 g) were mixed in a 50 mL solvent mixture of ethanol and acetone (1:1, v/v) followed by bath sonication for 10 min. The obtained mixture was kept on a water bath maintained at 60°C to make a clear solution of lipids and drug in an organic solvent system.…”
Section: Formulation Of Dox-gem Vcr Nlcsmentioning
confidence: 99%
“…Indeed, nanocarriers such as lipid micelles (Neuberg et al, 2015), solid lipid nanoparticles (Mukherjee et al, 2009;Bunjes, 2010), nanostructured lipidic carriers (NLCs) (Khan et al, 2015) and lipid nanocapsules (Sánchez-Moreno et al, 2012) have already been reported to hold immense promise for oral delivery of poorly water-soluble bioactives. Amongst these nanocarriers, the NLCs are considered to be of wider interest owing to their high drug-loading efficiency and drug stability (Naseri et al, 2015;Shah et al, 2016). Accordingly, the current work on the proposed novel technology was undertaken, wherein the PLCs of Mgf were incorporated into NLCs, for further enhancing the biopharmaceutical attributes.…”
Section: Introductionmentioning
confidence: 99%